Enhancing Expressive Communication in Children with ASD Through a NAO Robot-Mediated PECS-Adapted System - Santos, Luiziane Paulino dos; Silva, José Fagner da; Alves Filho, Sebastião Emídio; Souza, Anderson Abner; Paradeda, Raul Benites (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
Children with Autism Spectrum Disorder (ASD) often face significant challenges in verbal communication and social interaction, impacting their educational inclusion. This project paper outlines a proposed intervention to address these challenges by integrating social robotics with an adapted Picture Exchange Communication System. We propose the use of the NAO V6 humanoid robot as a mediator for a PECS-Adapted system, wherein children utilize visual cards featuring QR codes to express actions, desires, and feelings. The robot is designed to recognize these QR codes, verbalize the corresponding message, and provide interactive feedback. This research, grounded in the Design Science Research framework, will involve a qualitative, exploratory study with five children with ASD, aged 5–10 years, over a two-month period. The intervention aims to enhance expressive communication, increase communicative spontaneity, and facilitate social interaction, ultimately promoting more effective school inclusion. This paper details the system architecture, proposed methodology, and expected contributions of this novel approach within the Brazilian educational context.